In a house of lies [compact disc, unabridged] - Rankin, Ian (Rankin, Ian. Inspector Rebus novel series., 2018)
Rebus' retirement is disrupted once again when skeletal remains are identified as a private investigator who went missing over a decade earlier. The remains, found in a rusted car in the East Lothian woods, not far from Edinburgh, quickly turn into a cold case murder investigation. Rebus' old friend, Siobhan Clarke is assigned to the case, but neither of them could have predicted what buried secrets the investigation will uncover.